Factors associated with dental admissions for children aged under 5 years in Western Australia. Issue 7 (5th December 2008) - Slack-Smith, L; Colvin, L; Leonard, H; Kilpatrick, N; Bower, C; Messer, L Brearley
Abstract : Objective: There is limited literature describing dental admissions in preschool children. This paper describes dental hospital admissions and associated factors in children aged under 5 years. Design: This study uses total population data for Western Australia, which link midwives' information with birth defects, intellectual disability, hospital admissions and deaths. Children born 1980–1995 (n = 383 665) were followed until 5 years. Intellectual disability data were available for children born between 1983 and 1992. Admission data including length of stay were examined. Outcome measures: Admissions for each relevant 9th Revision of the International Classification of Diseases, Clinical Modification (ICD-9) principal diagnosis category and factors associated with having had a dental admission (all categories) and ICD-9 521 (mostly caries) in particular were investigated. Results: There were 11 523 dental admissions involving 10 493 children. Of all dental admissions, 76% were in ICD-9 category 521, which included admissions for dental caries. After adjusting for confounders, children with intellectual disability (odds ratio 1.92; 95% CI 1.63 to 2.27) and birth defect 1.85 (1.68 to 2.05) were more likely to have had a dental admission. Children living in a region without fluoridated water were also more likely to have had a dental admission 2.16 (1.94 to 2.40). Males were more likely to have had a dental admission 1.16 (1.08 to 1.25), as were children with an indigenous mother 1.17 (1.02 to 1.34). Investigation of ICD-9 521 admissions showed associations similar to those described above except for mother being indigenous, which was associated with reduced likelihood of admission. Conclusion: Given the burden of dental admissions in young children, these findings highlight the need for improved oral care for children.